Organic/inorganic double-precursor cross-linked alumina aerogel with high specific surface area and high-temperature resistance. Issue 12 (15th June 2022) - Wang, Xiaodong; Tian, Yulin; Yu, Chenglong; Liu, Lin; Zhang, Ze; Wu, Yu; Shen, Jun
Abstract: Alumina aerogel has drawn a great research interest in the aerogel community owing to its great high-temperature heat resistance. The typical preparation can be divided into two approaches depending on the type of precursors. However, the alumina aerogel derived from organic aluminum alkoxides suffers from poor monolithic integrity, whereas the one from inorganic aluminum salts presents unsatisfied thermal stability. In this work, we develop a novel organic/inorganic double-precursor cross-linking method to prepare alumina aerogels. Aluminum chloride hexahydrate is used to provide an acid condition for the hydrolysis and condensation reaction of aluminum sec -butoxide (ASB), and serves as a reactant to co-condensate with the hydrolyzed ASB to form an interpenetrating chain structure. The resulting alumina aerogel exhibits a high specific surface area (SSA) of 667 m 2 /g and good high-temperature thermal insulation performance. Moreover, it can still retain SSA of 224 and 105 m 2 /g after heating at 1000 and 1300°C, respectively. Graphical abstract: Image 1